2011
DOI: 10.1007/s10236-011-0493-5
|View full text |Cite
|
Sign up to set email alerts
|

Decadal scale variability of sea surface temperature in the Mediterranean Sea in relation to atmospheric variability

Abstract: Twenty-four years of AVHRR-derived sea surface temperature (SST) data and 35 years of NOCS (V.2) in situ-based SST data were used to investigate the decadal scale variability of this parameter in the Mediterranean Sea in relation to local air-sea interaction and large-scale atmospheric variability. Satellite and in situ-derived data indicate a strong eastward increasing sea surface warming trend from the early 1990s onwards. The satellite-derived mean annual warming rate is about 0.037°C year -1 for the whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
137
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 37 publications
36
137
6
Order By: Relevance
“…This rate is consistent with the trend obtained for the SST, where a lower rate (0.026 ºC/year) has been registered for the period 1985-2009, which translates into an overall increase of 0.7 ºC in 25 years. The annual warming rate in SST is in agreement with the findings of Nykjaer (2009), López García and Camarasa (2011) and Skliris (2012) for the western Mediterranean, who gave a rate of about 0.03 ºC/year for about the same period; and with the trends given by Macías et al (2013) for the whole Mediterranean (0.037 ºC/year). Although the warming of the climate system since the middle of the 19th century is accepted by almost all scientists, the observed trends in oceanic SST differ depending on the ocean, the period of reference and also the database employed in the analysis.…”
Section: Discussionsupporting
confidence: 79%
“…This rate is consistent with the trend obtained for the SST, where a lower rate (0.026 ºC/year) has been registered for the period 1985-2009, which translates into an overall increase of 0.7 ºC in 25 years. The annual warming rate in SST is in agreement with the findings of Nykjaer (2009), López García and Camarasa (2011) and Skliris (2012) for the western Mediterranean, who gave a rate of about 0.03 ºC/year for about the same period; and with the trends given by Macías et al (2013) for the whole Mediterranean (0.037 ºC/year). Although the warming of the climate system since the middle of the 19th century is accepted by almost all scientists, the observed trends in oceanic SST differ depending on the ocean, the period of reference and also the database employed in the analysis.…”
Section: Discussionsupporting
confidence: 79%
“…4 shows the SST trend clustering, from this map it can be seen that the warming is not uniform across the basin; two main regions appear with different warming intensity. The lower, but still positive, warming trend is found in the central Mediterranean around Italy (most of Tyrrhenian and Ionian basins) and parts of Algerian and Morocco coast, being higher in the centre and north of the Western Mediterranean while the highest warming is located in the Levantine basin, in agreement with the studies of Nykjaer (2009), Skliris et al (2012) and Shaltout and Omstedt (2014) that found higher values for SST trend in the eastern Mediterranean basin.…”
Section: Trendssupporting
confidence: 79%
“…To check the consistency of these results with SST trends previously found by other authors, we have run the trend analysis for different periods inside our database temporal span. The total SST increase derived from our analysis for the 1985-2008 period, trend of (1.06 ± 0.17) 9 10 -4°C /day, for the whole Mediterranean basin gives a value of 0.93°C, which is in good agreement with the 0.89°C value found in Skliris et al (2012), although this latter value was calculated for monthly SST versus our daily data. There is also good agreement with the trend calculated by Shaltout and Omstedt (2014) for the 1982-2012 period yielding a value of 0.35°C/decade while in our case it would be of 0.36°C/decade.…”
Section: Trendssupporting
confidence: 71%
See 1 more Smart Citation
“…Recent studies [Criado-Aldanueva et al, 2008;Nykjaer, 2009, Skliris et al, 2012 based on satellite-derived SST data have shown that during roughly the last two decades there has been a sea surface warming trend of about 0.4-0.6 C/decade over the EMed and Aegean Seas. This warming effect could enhance stratification thus reducing DWF rates.…”
Section: Cretan Straits Exitmentioning
confidence: 99%